Molecular characterization of cowpea breeding lines for Striga resistance using SCAR markers - Omoigui, L.O.; Yeye, M.; Ousmane, B.; Gowda, B.; Timko, M.P. (2012)
S. gesnerioides (Willd) Vatke is a major biological constraint to cowpea production in the dry savanna of sub-Saharan Africa. Yield losses caused by S. gesnerioides in these regions are estimated in millions of tons annually, and prevalence of Striga soil infestation is steadily increasing. The availability of molecular markers tightly linked to S. gesnerioides resistance genes opens up the possibility of applying Marker-Assisted Selection (MAS) to cowpea and would fast track the process of developing resistance varieties to the parasite. In the present study, we report the use of Fast Technology for Analysis (FTA) also known as PlantSaver Cards (Whatman® FTA), developed by Flinder Technology associate to retrieve DNA from plant tissue for molecular analysis. A total of 100 F2 individual plants derived from two crosses were validated for SG3 resistance using two different SCAR markers (MahSe2 and C42B) linked to Striga race 3 (SG3) and 5 (SG5) resistance in other segregating populations. Genomic DNA was successfully recovered from leaf tissues of cowpea pressed onto FTA classic card and the DNA obtained from the FTA papers was found to be suitable for molecular analysis by PCR-based techniques. The marker efficiency of SCAR MahSe2 and C42B in detecting SG3 resistance was 98.5% and 93% respectively. This result revealed the utility of SCAR markers in cowpea breeding programme. Therefore, the application of MAS using FTA technology has the potential to increase efficiency of selection and for molecular characterization of cowpea lines for Striga resistance.